2018
DOI: 10.7150/jca.21044
|View full text |Cite
|
Sign up to set email alerts
|

miR-149 in Human Cancer: A Systemic Review

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that regulate post-transcriptional gene expression via binding to the 3'-untranslated region (3'-UTR) of targeted mRNAs. They are reported to play important roles in tumorigenesis and progression of various cancers. Among them, miR-149 was confirmed to be aberrantly regulated in various tumors. In this review, we provide a complex overview of miR-149, particularly summarize the critical roles of it in cancers and expect to lay the foundation for future works on this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 102 publications
1
45
0
Order By: Relevance
“…According to our findings, this immunosuppressive niche found in G3 is potentially regulated by miRNAs that can modulate the expression of important genes both at intracellular and intercellular levels through, in this last case, tumor-derived extracellular vesicles as mediators of cell-cell communication. One example that potentially contributes to the immunosuppressive phenotype found in G3 is the highly expressed mir-149, which has already been reported as dysregulated in many types of cancer including melanoma, where its upregulation influences the expression of both oncogenes and tumor suppressor genes [48]. In this study, we showed that the inhibition of its target, NLRC5, interferes with neo-antigen presentation, in agreement with other studies where it has been associated with immune evasion mechanisms and considered as a biomarker of immune surveillance [18].…”
Section: Discussionmentioning
confidence: 99%
“…According to our findings, this immunosuppressive niche found in G3 is potentially regulated by miRNAs that can modulate the expression of important genes both at intracellular and intercellular levels through, in this last case, tumor-derived extracellular vesicles as mediators of cell-cell communication. One example that potentially contributes to the immunosuppressive phenotype found in G3 is the highly expressed mir-149, which has already been reported as dysregulated in many types of cancer including melanoma, where its upregulation influences the expression of both oncogenes and tumor suppressor genes [48]. In this study, we showed that the inhibition of its target, NLRC5, interferes with neo-antigen presentation, in agreement with other studies where it has been associated with immune evasion mechanisms and considered as a biomarker of immune surveillance [18].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs hsa-miR-149-5p, hsa-miR-125a-5p, hsa-miR-1827 in our 15 FFLs were found to regulate tumor suppression cell migration, invasion and apoptosis in the lung carcinomas with lesion formation. [77,78]. Hence these miRNAs can be studied and their role in tissue necrosis in nSARS-CoV-2 infection can be explored.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-149-5p was demonstrated to have dual roles in tumor, function as either tumor suppressor or oncogene. 23 MiR-149-5p expression profile was analyzed in lung cancer tissue and control tissues and the result exhibited that lung cancer tissues had significantly lower levels of miR-149-4p ( Figure 5B). Intriguingly, Pearson correlation analysis revealed that B3GNT3 expression was negatively associated with miR-149-5p expression ( Figure 5C).…”
Section: B3gnt3 Is Negatively Regulated By Mir-149-5pmentioning
confidence: 99%